2012
DOI: 10.4025/actasciagron.v34i2.12488
|View full text |Cite
|
Sign up to set email alerts
|

Chemical fertilization, organic fertilization and pyroligneous extract in the development of seedlings of areca bamboo palm (Dypsis lutescens)

Abstract: ABSTRACT. The effect of using chemical fertilization, organic and pyroligneous extract (EPL) on the seedling development of areca bamboo palm was evaluated. Treatments were: T1 = no fertilizer (control), T2 = 0.1% EPL, T3 = 0.2% EPL, T4 = NPK-20-5-20, T5 = NPK-20-5-20 + 0.1% EPL, T6 = NPK-20-05-20 + 0.2% EPL, T7 = castor bean cake, T8 = castor bean cake + 0.1% EPL and T9 = castor bean cake + 0.2% EPL. The EPL solutions were 0.1 or 0.2%, 100 mL per pot, applied every two weeks. NPK 20-5-20 chemical fertilizer w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 12 publications
1
4
0
4
Order By: Relevance
“…The aforementioned results of fertilization are in harmony with those attained by Younis et al (2004) on Jasminum grandiflorum, El-Naggar and El-Nasharty (2009) on Hippeastrum vittatum, Abd El-All (2011) on Aspidistra elatior, Ghatas and Abdallah (2016) on Echinacea purpurea, Rodrigo et al (2011) on Pinus nigra and Betula papyrifera, Habib(2012) on Caryota mitis Lour, Ghatas (2020) on coriander, Wanderley et al (2012) on areca bamboo palm (Dypsis lutescens), Youssef and Abd El-Aal (2014) on Hippeastrum vittatum, Youssef (2014) on Beaucarnea recurvata and Mazhar and Eid (2016) on Gladiolus grandiflorus, Ghatas (2016) stated that adding NPK chemical fertilizer at 4 or 6 g/plant on Gladiolus grandiflorus significantly increased leaf N, P, K and total carbohydrates content. Also, Mohamed (2018) demonstrated that using kristalon fertilizer at 8 g/pot produced the best values of leaves contents of N, P, K % and photosynthetic pigments of Dypsis cabadae.…”
Section: Chemical Compositionsupporting
confidence: 79%
“…The aforementioned results of fertilization are in harmony with those attained by Younis et al (2004) on Jasminum grandiflorum, El-Naggar and El-Nasharty (2009) on Hippeastrum vittatum, Abd El-All (2011) on Aspidistra elatior, Ghatas and Abdallah (2016) on Echinacea purpurea, Rodrigo et al (2011) on Pinus nigra and Betula papyrifera, Habib(2012) on Caryota mitis Lour, Ghatas (2020) on coriander, Wanderley et al (2012) on areca bamboo palm (Dypsis lutescens), Youssef and Abd El-Aal (2014) on Hippeastrum vittatum, Youssef (2014) on Beaucarnea recurvata and Mazhar and Eid (2016) on Gladiolus grandiflorus, Ghatas (2016) stated that adding NPK chemical fertilizer at 4 or 6 g/plant on Gladiolus grandiflorus significantly increased leaf N, P, K and total carbohydrates content. Also, Mohamed (2018) demonstrated that using kristalon fertilizer at 8 g/pot produced the best values of leaves contents of N, P, K % and photosynthetic pigments of Dypsis cabadae.…”
Section: Chemical Compositionsupporting
confidence: 79%
“…Dados semelhantes foram observados, em condições de campo, por Ichikawa & Ota (1982), que constataram melhor desenvolvimento da parte aérea das mudas de arroz com a aplicação do extrato pirolenhoso no solo. Ainda, a adição de EP na adubação orgânica isolada de areca-bambu proporcionou maiores alturas de planta (Wanderley et al, 2012).…”
Section: Resultsunclassified
“…No Brasil, alguns trabalhos foram desenvolvidos com o uso desse insumo em agricultura, como por exemplo, nas culturas do limoeiro 'cravo' (Zanetti et al, 2004), do eucalipto (Souza- Silva et al, 2006), da alface e do quiabo (Mascarenhas et al, 2006a(Mascarenhas et al, , 2006b), de mudas de pinus (Porto et al, 2007), de alface (Roel et al, 2007), de couve-de-folha (Shingo & Ventura, 2009), de orquídeas Cattleya intermedia e Miltonia clowesii, em que ocorreu um incremento do desenvolvimento vegetativo e radicular das espécies, ao utilizarem extrato pirolenhoso, acrescido ao substrato (Schnitzer et al, 2010) e de mudas de areca-bambu (Wanderley et al, 2012).…”
Section: Introductionunclassified
“…As reported by Tsuzuki et al (2000), under field conditions the application of pyroligneous acid can activate substances of plant secondary metabolism, inducing resistance to pests. Therefore, the effect of pyroligneous acid in the control of A. gemmatalis may be linked to the synthesis of metabolites involved in the mechanism of plant defense, since, in addition to the pyroligneous extract presenting in its composition phenolic compounds, it presents in larger part as a constituent acetic acid, which is part of the mevalonic acid biosynthetic pathway, a precursor in the synthesis of terpenes, which are essential metabolites in the defense mechanisms of plants against attack by herbivorous insects.…”
Section: Resultsmentioning
confidence: 82%
“…Its qualities have been known for decades in Japan and were disseminated in Brazil by immigrants from that country, especially in meetings of the Association of Natural Agricultural Producers (APAN) (FAPEMIG, 2005), being used as "organic fertilizer" in rice (Oryza sativa L.) (Tsuzuki et al, 2000), sorghum (Sorghum bicolor L.) (Esechie et al, 1998) and sweet potato (Ipomoea batatas L.) (Shibayama et al, 1998), and as a nematicide (Cuadra et al, 2000) and fungicide (Numata et al, 1994). Recently, Petter et al (2012) found positive effects of pyroligneous acid as a reducer of pH efficient at stabilizing spray pesticides.…”
mentioning
confidence: 99%